2019
DOI: 10.1111/joa.13119
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow rate and wall shear stress in seven major cephalic arteries of humans

Abstract: Blood flow rate (trueQ˙) in relation to arterial lumen radius (ri) is commonly modelled according to theoretical equations and paradigms, including Murray’s Law (trueQ˙ ∝ ri3) and da Vinci’s Rule (trueQ˙ ∝ ri2). Wall shear stress (τ) is independent of ri with Murray’s Law (τ ∝ ri0) and decreases with da Vinci’s Rule (τ ∝ ri-1). These paradigms are tested empirically with a meta‐analysis of the relationships between trueQ˙ and ri in seven major arteries of the human cephalic circulation from 19 imaging studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Using the devices in series allowed modeling of multiple tissue barriers in a connected system. To further assess the device flow, sheer stress was calculated using the Navier–Stokes equation ( Seymour et al , 2020 ). At a flow rate of 2.94 μ l min −1 , the cells were subjected to 4.0 × 10 −3 dyn cm −2 shear stress.…”
Section: Resultsmentioning
confidence: 99%
“…Using the devices in series allowed modeling of multiple tissue barriers in a connected system. To further assess the device flow, sheer stress was calculated using the Navier–Stokes equation ( Seymour et al , 2020 ). At a flow rate of 2.94 μ l min −1 , the cells were subjected to 4.0 × 10 −3 dyn cm −2 shear stress.…”
Section: Resultsmentioning
confidence: 99%
“…In the fluid, inlet velocities and outlet pressure conditions were prescribed as follows: where was built based on the waveform plotted in Figure 2 , corresponding to an averaged internal carotid pulse reported by [ 38 ]. It was prefixed with a s linear ramp for a smoother initialization and scaled to reach an average flow rate of 4 mL·s −1 , which correponded to the mean ICA flow measured among 13 studies, as reported in a recent review [ 39 ].…”
Section: Materials and Methodsmentioning
confidence: 99%
“…where V(t) was built based on the waveform plotted in Figure 2, corresponding to an averaged internal carotid pulse reported by [38]. It was prefixed with a 0.2 s linear ramp for a smoother initialization and scaled to reach an average flow rate of 4 mL•s −1 , which correponded to the mean ICA flow measured among 13 studies, as reported in a recent review [39]. At the outflow, unlike in typical CFD simulations, the absolute value of the pressure was of major importance.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…(Online version in colour.) [25]. Thus, the ICAs account for 88%, and the VAs account for 12%, of total cerebral perfusion.…”
Section: (A) Brain Perfusion In Extant Haplorhine Primatesmentioning
confidence: 99%
“…Although the ICAs supply approximately 75%, and the VAs 25%, of total brain perfusion ð _ Q TOTAL Þ in humans [25][26][27][28][29][30][31], these proportions approach each other in extant haplorhine species with smaller brains until they become approximately equal in brains smaller than 10 ml. (See the electronic supplementary material, including figure S5, for a detailed analysis of the roles of the VAs and ICAs in extant haplorhines.)…”
Section: (A) Brain Perfusion In Extant Haplorhine Primatesmentioning
confidence: 99%